A Color Reaction of Wood with Methanol- Hydrochloric Acid - Isenberg, H.; Buchanan, M. A. (Indian Forester, 1946)
Tests by the authors with 277 species in 56 families have shown that methanol containing a small amount of hydrochloric acid gives a purple coloration when mixed cold with the shavings of some species and not with others. The method gives promise of making it possible to identify the woods of certain species that cannot be separated on the basis of structure alone. The authors will be glad to correspond with anyone desiring further information concerning the tests.